PENGARUH NAUNGAN MENGGUNAKAN PARANET TERHADAP PERTUMBUHAN SERTA KANDUNGAN KLOROFIL DAN β KAROTEN PADA KANGKUNG DARAT(Ipomoea reptans Poir) - Ika Wulandari; Sri Haryanti; Munifatul Izzati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Kangkung is one of the of the most favourite vegetable of Indonesian people. Most of indonesian including low-class to high-class like to consume it. Kangkung is often coocked as many different kind of dish such as, gado-gado, tumis kangkung, sayur bening, pecel. That is the proof from social side that Indonesian people can accept kangkung to become daily consumption. The purpose of this research is to analyze the effect of shade on growth, chlorophyll, carotenoid content of kangkung. The Parameters were plant height, number of leaf, root length, fresh weight of plant, number of stomata, chlorophyl content and β carotene content. This research was conducted at the Laboratory of the BSF Plant of Department of Biology Undip FSM. This research ks designed using shade as one factor RAL. Data analysis was using ANOVA at significance level of 95%, if there is significant difference than continued with Duncan Multiple Range Test (DMRT). The results show that different shade makes no significant different on plant height, number of leaf, fresh weight of plant, number of stomata, β carotene content but tend to increase yet decrease chlorophyll content. Using shade with two layers of paranet result in the lowest of chlorophyl content, but the most of β carotene content if compared to the others treatment.Keyword : shade, kangkung, chlorophyll, β carotene